Biochemical characterization and identification of ferulenol and embelin as potent inhibitors of malate:quinone oxidoreductase from Campylobacter jejuni - Kabongo, Augustin Tshibaka; Acharjee, Rajib; Sakura, Takaya; Bundutidi, Gloria Mavinga; Hartuti, Endah Dwi; Davies, Cadi; Gundogdu, Ozan; Kita, Kiyoshi; Shiba, Tomoo; Inaoka, Daniel Ken (Frontiers in Molecular Biosciences, 2023)
Campylobacter jejuni infection poses a serious global threat to public health. The increasing incidence and antibiotic resistance of this bacterial infection have necessitated the adoption of various strategies to curb this trend, primarily through developing new drugs with new mechanisms of action. The enzyme malate:quinone oxidoreductase (MQO) has been shown to be essential for the survival of several bacteria and parasites. MQO is a peripheral membrane protein that catalyses the oxidation of malate to oxaloacetate, a crucial step in the tricarboxylic acid cycle. In addition, MQO is involved in the reduction of the quinone pool in the electron transport chain and thus contributes to cellular bioenergetics. The enzyme is an attractive drug target as it is not conserved in mammals. As a preliminary step in assessing the potential application of MQO from C. jejuni (CjMQO) as a new drug target, we purified active recombinant CjMQO and conducted, for the first time, biochemical analyses of MQO from a pathogenic bacterium. Our study showed that ferulenol, a submicromolar mitochondrial MQO inhibitor, and embelin are nanomolar inhibitors of CjMQO. We showed that both inhibitors are mixed-type inhibitors versus malate and noncompetitive versus quinone, suggesting the existence of a third binding site to accommodate these inhibitors; indeed, such a trait appears to be conserved between mitochondrial and bacterial MQOs. Interestingly, ferulenol and embelin also inhibit the in vitro growth of C. jejuni, supporting the hypothesis that MQO is essential for C. jejuni survival and is therefore an important drug target.